ANALISIS YURIDIS SANKSI PIDANA KEKERASAN PSIKIS TERHADAP PEREMPUAN DALAM UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - IDAWATI '; Dessy Artina; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Domestic violence or what is known as domestic violence often occurs even though Law No. 23 of 2004 concerning the elimination of domestic violence (PKDRT) has occurred. Cases of domestic violence are increasing year by year, especially against women (wives). In domestic violence there is physical violence, psychological violence, sexual violence and economic violence.. The purpose of this thesis writing is: First, Regulation of criminal sanctions on psychic violence within the household based on Law Number 23 of 2004 concerning PKDRT, Second, Proof of victims of psychic violence according to Law Number 23 of 2004 concerning PKDRT, Third, An ideal regulation on criminal sanctions against victims of psychic violence according to Law Number 23 of 2004 concerning PKDRT.This type of research can be classified in the type of normative legal research, because in this study the authors conducted research by examining library materials. Data sources used are secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials.From the results of the research problem there are three main things that can be concluded. First, by referring to Article 10 of the Criminal Code, then in Law Number 23 of 2004 the sanctions imposed on perpetrators of psychic violence are imprisonment and fines. Additional crimes are not the same. Second, the most easily available evidence is